2021
DOI: 10.1136/thoraxjnl-2020-216749
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal hypoxaemia in interstitial lung disease: a systematic review

Abstract: BackgroundPatients with interstitial lung disease (ILD) are at risk of developing nocturnal hypoxaemia due to ventilatory restriction and impaired gas exchange that worsen with supine posture and reduced ventilatory drive during sleep. This systematic review synthesised literature on the diagnostic evaluation, epidemiology, associations, management and prognosis of nocturnal hypoxaemia in ILD.MethodsOvid MEDLINE, Embase and CENTRAL databases were searched for eligible studies. Meta-analyses with subgroup analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…A number of studies have confirmed the high degree of sleep‐related hypoxaemia in IPF/ILD patients, and furthermore, have shown associations between nocturnal hypoxaemia and the development of PH and increased mortality in these cohorts 110,124,125 . Nocturnal oxygen desaturation occurs as a direct consequence of OSA but may also relate to other physiologic derangements of ventilation and gas exchange in patients with IPF/ILD 126 …”
Section: Pharmacological Therapymentioning
confidence: 94%
See 4 more Smart Citations
“…A number of studies have confirmed the high degree of sleep‐related hypoxaemia in IPF/ILD patients, and furthermore, have shown associations between nocturnal hypoxaemia and the development of PH and increased mortality in these cohorts 110,124,125 . Nocturnal oxygen desaturation occurs as a direct consequence of OSA but may also relate to other physiologic derangements of ventilation and gas exchange in patients with IPF/ILD 126 …”
Section: Pharmacological Therapymentioning
confidence: 94%
“…110,124,125 Nocturnal oxygen desaturation occurs as a direct consequence of OSA but may also relate to other physiologic derangements of ventilation and gas exchange in patients with IPF/ILD. 126 Whilst very little high-quality IPF/ILD-specific evidence is available, general OSA interventional studies provide a framework for initiating therapy. It is reasonable for continuous positive airway pressure (CPAP) to be considered for patients with moderate to severe OSA, particularly in those with daytime somnolence.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
See 3 more Smart Citations